Deciphering Oxygen Isotope Records From Chinese Speleothems With an Isotope‐Enabled Climate Model. Issue 12 (19th December 2019) - Hu, Jun; Emile‐Geay, Julien; Tabor, Clay; Nusbaumer, Jesse; Partin, Judson
Abstract: Speleothem δ 18 O is widely used to reconstruct past hydroclimate variability, particularly over Asia. However, the interpretation of this proxy is still in debate. While this proxy is originally interpreted as regional rainfall amount of the Asian monsoon, other studies have interpreted it as upstream monsoon rainfall or atmospheric circulation changes. To better understand the signal preserved in speleothems over various time scales, this study employs a state‐of‐the‐art isotope‐enabled climate model to quantify contributions to the oxygen isotope composition of precipitation ( δ 18 O P ) over China. Results suggest that orbital‐scale speleothem δ 18 O variations at Chinese sites mainly record the meridional migration of the Asian monsoon circulation, accompanied by an early northward movement of the East Asian rain belt. At interannual scales, Chinese speleothem δ 18 O is also tied to the intensity of monsoonal circulation, via a change in moisture source locations: Enhanced moisture delivery from remote source regions leads to more negative δ 18 O P, particularly in late summer and early autumn. Our results have implications for the hydroclimatic interpretation of speleothem δ 18 O from Chinese caves and suggest that this interpretation is time scale dependent. Key Points: At orbital scales, Chinese speleothem oxygen isotopes mainly represent the meridional migration of the East Asian monsoon circulation At orbital scales, low values of Chinese speleothem oxygen isotopes are associated with early northward movement of the East Asian rainbelt At interannual scales, Chinese speleothem oxygen isotope ratios are mainly controlled by the change of moisture source locations